2014
DOI: 10.1002/jcla.21715
|View full text |Cite
|
Sign up to set email alerts
|

Is Neutrophil Lymphocyte Ratio an Indicator for Proteinuria in Chronic Kidney Disease?

Abstract: In conclusion, NLR, a parameter easily found in routine blood counts of CKD patients, is a marker with prognostic value for the presence and degree of proteinuria.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
30
1
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(34 citation statements)
references
References 16 publications
1
30
1
2
Order By: Relevance
“…The NLR has been added to the arsenal of prognostic biomarkers and has proven to be a useful objective indicator of inflammation in several diseases such as critical illness, malignancy, soft tissue sarcoma, trauma, diabetes mellitus, heart disease, and chronic kidney diseases . For example, Xue et al reported that higher NLR levels were associated with greater risk of stroke severity on admission, unfavorable outcomes, and recurrent acute ischemic stroke .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The NLR has been added to the arsenal of prognostic biomarkers and has proven to be a useful objective indicator of inflammation in several diseases such as critical illness, malignancy, soft tissue sarcoma, trauma, diabetes mellitus, heart disease, and chronic kidney diseases . For example, Xue et al reported that higher NLR levels were associated with greater risk of stroke severity on admission, unfavorable outcomes, and recurrent acute ischemic stroke .…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have explored the triad of disease/injury, systemic inflammation, and malnourishment. The stress released by disease/injury and metabolism and comorbidities altered by the inflammatory response and malnourishment make the triad highly associated with risk of mortality . One plausible mechanism through which EN may mitigate inflammation is via interactions with the gut‐associated lymphoid tissue (GALT).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In conclusion, we consider that NLR and PLR are good markers of microalbuminuria, easy and inexpensive to obtain by means of a blood count [4,5]. However, it should be evaluated in future research taking into account the aforementioned methodological considerations.…”
Section: Dear Editormentioning
confidence: 99%
“…Chronic renal disease (CKD), and end-stage renal disease (ESRD) in particular, are associated with high mortality rates due to complications caused by cardiovascular diseases (CVDs) (Binnetoğlu et al, 2014), infections (Petrie et al, 2007;Reddan et al, 2003) and other inflammatory processes due to hypodynamic forces (Lavin-Gomez et al, 2011;Okyay et al, 2013).…”
Section: Introductionmentioning
confidence: 99%